Total synthesis of the Fusarium toxin equisetin. - Burke, LT; Dixon, D; Ley, S; Rodríguez, F (2005)
A short stereoselective synthesis of the Fusarium toxin equisetin, a potent inhibitor of HIV-1 integrase enzyme is described, using as the key step a stereoselective intramolecular Diels-Alder reaction of a fully conjugated E,E,E-triene with a trisubstituted gamma,delta-unsaturated beta-ketothioester.